Discovery of TNF-alpha as a therapeutic target in rheumatoid arthritis: preclinical and clinical studies. - Feldmann, M; Maini, R (2002)
The development of effective new treatments is greatly facilitated by the understanding of the mechanisms of disease. In rheumatoid arthritis, there has been progress in understanding its immunology, the HLA class II predisposition including the 'shared epitope' and more recently in understanding the importance of proinflammatory cytokines. Here we review our work in defining TNFalpha as a therapeutic target in rheumatoid arthritis, from an understanding of molecular pathogenesis in vitro, to formal proof in the clinic in vivo. There is now extensive clinical use of anti-TNFalpha biologicals for severe rheumatoid arthritis in the US and Europe.